Politique de déguerpissement et processus de restructuration des territoires de Libreville [Gabon] - Rano-Michel Nguema (L'Espace Politique)
Evictions are plentiful in sub-Saharan Africa. Libreville, capital of Gabon, does not make an exception to this rule. Since the 1970s, eviction appears as a fundamental step in the restructuring process of Libreville’s space where built up areas are growing fast and in an anarchic way. Urban growth, resulting from the oil boom, has led to saturation of central and semi-central districts, occupied mostly by informal settlements. The government response to what it considers as an illegal occupation is to eradicate slums, to dislodge people by force and then to remove them in the suburbs. What are the mechanisms and strategies used to operate these forced evacuations? What forms of resistance are manifested against this policy? What is the impact of such policies on the lives of citizens and on the town’s reorganization? In order to answer these questions, this paper proposes firstly to examine the policy of eviction in Libreville during the last 40 years, and secondly to present the actions and reactions of the actors of this struggle for land appropriation.